2018
DOI: 10.15171/apb.2018.016
|View full text |Cite
|
Sign up to set email alerts
|

Teucrium polium Extract Enhances the Anti-Angiogenesis Effect of Tranilast on Human Umbilical Vein Endothelial Cells

Abstract: Purpose: Angiogenesis plays an important role in numerous pathophysiological events like cancer. As a result of this, tranilast as an anti-fibrotic drug induces the promising antitumor activities through the inhibition of angiogenesis. Further, Teucrium polium (TP) is a herbal medicine (family Lamaceae) with antitumor properties. This study was conducted to investigate the combination effects of tranilast and T. polium on human umbilical vein endothelial cells (HUVECs) viability and apoptotic genes expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…They could successfully report a higher cell death rate in the combination therapy using anticancer drugs, including vincristine, doxorubicin, and vinblastine. Shikhbahaei et al (22), demonstrated that a combination of PE fraction of T. polium with tranilast, an anti-angiogenesis substance, decreased angiogenesis and its related genes significantly. Cell arrest at the S phase was postulated as the main molecular mechanism for the cytotoxic potential of T. polium.…”
Section: Discussionmentioning
confidence: 99%
“…They could successfully report a higher cell death rate in the combination therapy using anticancer drugs, including vincristine, doxorubicin, and vinblastine. Shikhbahaei et al (22), demonstrated that a combination of PE fraction of T. polium with tranilast, an anti-angiogenesis substance, decreased angiogenesis and its related genes significantly. Cell arrest at the S phase was postulated as the main molecular mechanism for the cytotoxic potential of T. polium.…”
Section: Discussionmentioning
confidence: 99%
“…No lesions (pathological abnormalities) were observed in these organs.Our findings are in agreement with previous studies on the biochemical and haematological responses of Wistar rats to Pterocarpus santalinus. 26,27 Additionally, studies have shown that fresh and dried leaves of Pterocarpu ssantalinus contain alkaloids, flavonoids, glycosides, saponins, tannins, phenolics and triterpenoids. 28,29 The antioxidant activity of some of the secondary metabolites such as saponins, tannins, phenols and triterpenoids present in the plant may be responsible for their ability to reduce necrotic tissue in the organs (brain and heart) investigated.…”
Section: Effect Of Pterocarpus Santalinus Ethanol Leaf Extract On The...mentioning
confidence: 99%
“…The cell cytotoxicity was evaluated by MTT method according to the published method. 18 Briefly, 5 Â 10 3 cancer cells per well were seeded in 96-well plates and incubated for 24 h.…”
Section: Cell Proliferation Analysis and Immunization Of Cervical Carcinoma-bearing Micementioning
confidence: 99%